Politik dan Kebijakan Pembaharuan Pendidikan : Mencari Pijakan Operasional yang Akuntabel - Udik Dwi Wibowo (Dinamika Pendidikan, 2011)
Politics and policies of educational innovation are often viewed nasty, because it's  introduced and dominated by autoritative power  interests. In addition to, overlap of implementation was occur where one innovation work wobbly,  another     innovation  introduced,  which  is  make  confusing  to innovation adopter  units. Basically, educational innovation be intended to improve quality, relevance, eficiency and efectiveness of educational performance. But, such positive aspects were not always support by accountable implementation capacity, either at the educational organization level or individual level; so the noble "goalsof educational innovations often unrealizable.  Therefore,  it  required consciousness from  educational stakeholders to sinergize to execute the educational reforms.